Anesthesiology education: A discussion on the current reform for training in the hypoxic environment of the highlands of China - Chen, Hongyang; Wang, Zining; Zheng, Lan; Ciren, Jiumei; Zhang, Weiyi; Zhu, Tao (Frontiers in Education, 2023)
In recent decades, great changes have taken place in the anaesthesiology of China in anesthesia equipment, anesthesiology theory of basic, clinical research and clinical anesthesia technology. Despite this, there is still a shortage of doctors with higher medical education in anaesthesiology, which is also a major problem facing for anesthesia discipline of China, especially in Tibet, Xinjiang and Inner Mongolia and other regions. Due to the high cold and low oxygen environment in the Tibet Autonomous Region, the development of medical education is backward, especially anesthesia medical education. With the improvement of anesthesia medical technology, we should continue to optimize and reform the local anesthesia medical teaching methods, so as to make substantial reform of anesthesia medical education in Tibet. This paper discusses the main problems in anesthesia medical education and clinical anesthesia in Tibet, as well as its reform ideas and methods. It aims to improve the level of anesthesiology education in Tibet, so as to improve the clinical professional ability of doctor anesthesia, and then better benefit to the local people.